ADSORPSI LOGAM Cr(VI) PADA LIMBAH CAIR BATIK DENGAN ZEOLIT ALAM TERAKTIVASI - Dian Kresnadipayana; Sutarno Sutarno; Mohammad Masykuri (Biomedika, 2014)
ABSTRAK Zeolit alam mempunyai potensi sebagai penjerap logam berat dalam pengolahan limbah cair yang disebabkan oleh kapasitas penjerapan, selektivitasnya yang tinggi, dan jumlahnya melimpah di Indonesia. Zeolit alam diaktivasi secara fisika dengan pemanasan pada suhu 150 oC dan secara kimia dengan HCl 6 M dan NH4NO3 2 M. Variasi isian matrik adsorben pada kolom digunakan untuk mengetahui perbandingan besarnya adsorpsi dengan panjang unggun 10, 15, dan 20 cm. Kadar logam Cr(VI) pada sampel limbah cair sebesar 14,68 ppm. Berdasarkan Peraturan Daerah Provinsi Jawa Tengah no. 10 tahun 2004, limbah tersebut telah melebihi baku mutu air limbah. Hasil elusi satu kali dengan larutan K2Cr2O7 80 ppm pada kolom adsorpsi ZA-10, ZA-15 dan ZA-20 berturut-turut sebesar 98,07 %; 99,23 %; dan 99,96 %. Hasil elusi satu kali dengan sampel limbah cair batik kadar logam Cr(VI) 14,68 ppmpada kolom adsorpsi ZA-10, ZA-15 dan ZA-20 berturut-turut sebesar 98,45 %; 99,54 %; dan 99,97 %. Limbah cair batik setelah perlakuan telah memenuhi kriteria baku mutu air limbah ditinjau dari kandungan logam Cr(VI). Kata kunci: limbah cair batik, logam Cr(VI), adsorpsi, zeolit alam. ABSTRACT Nature zeolite are capable of removing quantities of heavy metals from wastewaters, that they have potential properties as adsorbent for capacity and selectivity. Meanwhile, Indonesia has wide and large-scale distribution of zeolite. It give easy access to these minerals for characterization with respect to their function as adsorbent. The naturalzeolite was activated physically by heating it at temperature of 150° C andchemically using 6 M HCl and NH4NO3 2 M. The variations of adsorbent matrix entry in the column were used to determine the ratio of the amount of adsorption with a bed length of 10, 15, and 20 cm. The value of metal Cr(VI) was found that in wastewater samples of 14,68 ppm. Based on Regulation of Central Java Province no. 10 of 2004, the wastewater has been passed the standards of quality wastewater. The one-time elution showed that a solution of 80 ppm K2Cr2O7 in each adsorption column ZA-10, ZA-15 and ZA-20 with value adsorption of 98,07%; 99,23 %; dan 99,96 % for the adsorbent adsorption, respectively. The one-time elution showed that wastewater samples the value of the metal Cr(VI) content of 14.68 ppm in each adsorption column ZA-10, ZA-15 and ZA-20 with value adsorption for 99.97%, 98.39% and 99.39 %98,45 %; 99,54 %; and 99,97 % for the adsorbent adsorption, respectively. The liquid waste of batik manufacturing after processing showed to meets the criteria of wastewater quality standard in terms of the metal Cr(VI) content. Key words: liquid waste of batik manufacturing, metal Cr(VI), adsorption,natural zeolite.